Zora and me - Bond, Victoria, 1979- (Candlewick Press, 2010)
A fictionalized account of Zora Neale Hurston's childhood with her best friend Carrie, in Eatonville, Florida, as they learn about life, death, and the differences between truth, lies, and pretending. Includes an annotated bibliography of the works of Zora Neale Hurston, a short biography of the author, and information about Eatonville, Florida.